Becoming Mrs. Lewis [large type] : the improbable love story of Joy Davidman and C.S. Lewis - Henry, Patti Callahan (Thorndike Press large print Christian fiction series., 2018)
When poet and writer Joy Davidman began writing letters to C. S. Lewis -- known as Jack -- she was looking for spiritual answers, not love. Love, after all, wasn't holding together her crumbling marriage. Everything about New Yorker Joy seemed ill-matched for an Oxford don and the beloved writer of Narnia, yet their minds bonded over their letters. Embarking on the adventure of her life, Joy traveled from America to England and back again, facing heartbreak and poverty, discovering friendship and faith, and against all odds, finding a love that even the threat of death couldn't destroy. In this exploration of one of the greatest love stories of modern times, we meet a brilliant writer, a fiercely independent mother, and a passionate woman who changed the life of this respected author and inspired books that still enchant us and change us. Joy lived at a time when women weren't meant to have a voice -- and yet her love for Jack gave them both voices they didn't know they had.